2020
DOI: 10.1149/2162-8777/aba0cf
|View full text |Cite
|
Sign up to set email alerts
|

Rotameric Isomers of La2@C80 & Dodecafluoro-Subphthalocyanine Conjugate: Computational Characterization

Abstract: Stability and spectra of rotamers of a previously via Prato reaction prepared conjugate of dimetallofullerene La2@C80 and dodecafluoro-subphthalocyanine with summary formula C113H10BF12La2N7O and bridging over the cage C–C bond between five- and six-membered rings are calculated. The inter-rotameric energetics is evaluated at the M06-2X/6-311G* ∼ SDD level while the entropy term with the M06-2X/3-21G ∼ SDD approach. The rotamer most-populated at room and higher temperatures has a structure in which both the ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Thus, it is hard to consider the encapsulated La atoms as purely trivalent. Similar charge population results are also reported in some recent studies, which all show a low La charge in their endofullerenes. , …”
Section: Resultssupporting
confidence: 90%
“…Thus, it is hard to consider the encapsulated La atoms as purely trivalent. Similar charge population results are also reported in some recent studies, which all show a low La charge in their endofullerenes. , …”
Section: Resultssupporting
confidence: 90%
“…On the other hand, the use of DND and DNP affected dramatically the quality of results (even if it was possible to achieve SCF convergence), producing, for example, an eclipsed conformation of double-decker complex instead of the typical staggered one. This observation adds to the known advantage of smaller basis sets when performing Mulliken population analysis (which also played an important part in the present study) of lanthanide-based molecular systems [76][77][78][79].…”
Section: Discussionmentioning
confidence: 68%
“…Geometry, electronic structure, electrochemical and spectroscopic features of SubPcs have been thoroughly investigated by theoretical calculations. 211–233 A detailed study on a series of three SubPc-Cl derivatives bearing different peripheral substituents ( i.e. perhydrogenated, trinitro- and tri- t -butyl SubPc) at Hartree–Fock (HF) and density functional theory (DFT) levels using STO-3G and 6-31G basis sets has been reported by Ferro et al 211 The calculated geometries of the unsubstituted derivative were found to be in accordance with the experimental data from X-ray diffraction studies, and no substantial changes were detected with respect to the substituted derivatives.…”
Section: Subphthalocyaninesmentioning
confidence: 60%